ASSESSMENT OF EFFECTIVENESS OF ANTI-RECURRENT AND HORMONAL THERAPY IN WOMEN WITH UTERINE FIBROIDS IN PREGRAVIDAL PREPARATION - V. A. KHOROLSKY; L. G. DRJAEVA; L. A. MEDVEDEVA; A. V. BARSUK; T. V. SAYNOGA (Кубанский научный медицинский вестник, 2018)
Aim. This study was designed to evaluate the effectiveness of sequential prescription of drugs for anti-recurrent therapy of the uterine fibroids (UF) and combined oral contraceptives (COC) in pregravidal preparation.Materials and methods. There was conducted a prospective, nonrandomized and controlled cohort study of 150 women with UF  who are planning a pregnancy after the organ-preserving treatment  of uterine fibroids by means of myomectomy with laparoscopic  access and pregravidal preparation. The immunohistochemical (IHC)  study of the intensity expression of Ki 67, p53, Bcl-2 was performed  for the differential diagnosis of reactive proliferation from dysplasia  in the distant fibroid node and the selection of anti-recurrent therapy.Results. The duration of the UF disease does not depend on the intensity of expression of p53, Ki-67 or Bcl-2, the level of expression  of the progesterone receptors in the distant fibroid node. A negative average correlation between the level of hemoglobin  before myomectomy, the duration of the disease (r = -0.3867) and  the number of nodes (r = -0.5389) was revealed. After the end of  the anti-recurrent treatment in women who underwent organ- preserving treatment of uterine fibroids, the prescription of COC is connected with a further decrease in the size of fibroid nodes remaining after myomectomy from 15.81±0.22 mm to 8.94±0.45  mm (p<0.05), the number of fibroid nodes from 2.25±0.08 to  0.91±0.06 (р<0.05).Conclusion. The combination of anti-recurrent therapy with the subsequent prescription of the COC for prevention of the UF growth  in women planning a pregnancy after myomectomy with endoscopic  access is highly effective.